Macroeconomic and Institutional Factors, Debt Composition and Capital Structure of Latin American Companies - Cláudio Bernardo; Tatiana Albanez; José Roberto Securato (BBR: Brazilian Business Review)
The objective of this research was to examine the influence of macroeconomic and institutional factors when determining the capital structure of Latin American companies from 2009 to 2014, and also analyze if the significance of these factors to explain the capital structure of the companies is changed taking into account the financing composition. We used hierarchical linear modeling to process data. The main results pointed that, both the representative variables of characteristics of the firm and representative variables of countries are important determinants of the capital structure of the companies. However the variables of the firm explain a much higher percentage of variance of leverage. Thus, we emphasize that there is still much to be done in order to analyze the effects of macroeconomic and institutional factors. We expect that this study has created contributions to the national literature, by using a theoretical and also econometric approach that has not been much explored so far. As well as for market agents to examine the determinants of capital structure, considering the institutional aspects.